Meeting the needs of women in the perinatal period, who use or are in treatment for using drugs: A mixed-methods systematic review - Emma Smith; Shirley Lewis; Lynne Gilmour; Louise Honeybul; Helen Cheyne; Narendra Aladangady; Brigid Featherstone; Margaret Maxwell; Joanne Neale; Mariana Gonzalez Utrilla; Polly Radcliffe (Health and Social Care Delivery Research)
Background Women who use and/or are in treatment for using drugs during the perinatal period have complex health and social care needs. Substance use in the perinatal period is multifaceted, with many confounding factors that may impact the long-term health and well-being of both mothers and children. Evidence is needed to identify which psychosocial interventions are effective for women who use and/or are in treatment for drug use during the perinatal period. Objective(s) (1) Describe the range of psychosocial interventions available for women who use and/or are in treatment for drugs in the perinatal period; (2) to document evidence on the effectiveness of interventions and (3) identify interventions that women feel most meet their needs. Design A mixed-methods systematic review was conducted following a predetermined protocol and the Joanna Briggs Institute guidance for mixed-methods systematic reviews, adopting a segregated approach. Review methods Eight databases were searched for articles meeting the inclusion criteria on 7 April 2022, and updated searches were run on 5 February 2024. The search was limited to include peer-reviewed articles published after 1990 and available in English. In total, 15,655 articles were identified. Following screening by four reviewers by title and abstract and then full text, 197 articles were included in the review. A data extraction template was used to extract study characteristics and results. Quality was assessed using the mixed-methods Quality Appraisal Tool. Cohen’s d was used to measure the effect size for quantitative data to understand if an intervention had a small (> 0.2), medium (> 0.5) or large effect (> 0.8). Effectiveness was measured through three outcomes: (1) improvements and engagement with and retention in substance use treatment services for women in the prenatal and postnatal period; (2) reductions in substance use by women in the perinatal period and (3) improvements in engagement with and retention in prenatal care. For qualitative data, articles were grouped by the intervention type and the authors’ analytical themes and conclusions were thematically synthesised. Results The 197 included studies described 217 separate interventions. Most interventions (85.3%) were community-based, delivered in more than one way (49.3%), and delivered in single settings (50.6%), although some were colocated alongside other services (22.1%). No conclusive evidence for effectiveness was established for any type of intervention, although most interventions that improved retention in substance use services included practical support. The qualitative synthesis supported these findings and additionally suggested that women appreciated being able to access multiple services in one place: non-judgemental, trauma-informed services and peer-support models. Limitations There were wide discrepancies in the types of information reported related to the age of some studies, limiting our ability to evaluate the effectiveness through quantitative analysis. The qualitative analysis was similarly limited as not all the identified qualitative papers included the views of women about treatment received. Conclusions Interventions that included practical support were found to be more effective in both the quantitative and qualitative findings. There is also some evidence for the effectiveness and feasibility of integrated, multidisciplinary interventions in both the quantitative and qualitative data. Future work There is a need for up-to-date, high-quality research studies into interventions for pregnant women who use and/or are in treatment for drug use. It is additionally important that the voices of women are considered in future research. Funding This article presents independent research funded by the National Institute for Health and Care Research (NIHR) Health and Social Care Delivery Research programme as award number NIHR130619. Plain language summary Introduction Women who use drugs, or who are in treatment for using drugs, during and after pregnancy often have health and social care needs that can poorly impact both mothers and children. This is complicated because women who use drugs during and after pregnancy might not respond to the treatment that is available for them. We wanted to find out which types of psychological and social therapy and support worked best for these women. What we did A systematic review takes a detailed look at the published research on a topic to make recommendations after looking at the evidence. We searched for articles that described psychological and social therapies and support for women who use drugs while pregnant. We included research from all countries and from the years 1991 to 2023. What we found We found 15,655 articles and, after checking them for relevance, included 197 in the review; 217 separate types of treatment were described within these articles. The treatments were mostly delivered to individuals and were community based. Analysis of the measurable, quantitative data did not show that any one intervention worked better than any other, although the findings did show that practical support, including support for child care, transportation and housing, was important in helping women to engage with treatment. Data from qualitative studies showed that women appreciated being able to access multiple services in one place and that they valued a non-judgemental approach from staff. Overall Women found practical support to be very useful, and there is also some evidence to show that ‘one-stop shops’ (where multiple services are located together) are helpful to women who use or are in treatment for drugs during and after pregnancy.